The Capability of Mangrove Charcoal in Adsorption Process of Indigosol Substance in Wastewater of Batik Industry - Maryudi, Maryudi; Salamah, Siti; Rahayu, Aster (Universitas Negeri Semarang, 2021)
The development of the textile industry has had a positive impact on economic growth in Indonesia. Batik is one of the products of the textile industry that is proliferating in Indonesia. Dyes are the main ingredients in the textile and batik industrial process. One of the dyes used is indigosol, and about 15% of the total dyes used will result in industrial liquid waste. The presence of these dyes can damage the water and soil ecosystems. Liquid sewage treatment is needed to minimize the amount of contamination against groundwater and surface water. A standard method used in the handling of liquid waste is by adsorption process with various adsorbents. Commonly used adsorbents are silica gel, activated alumina, zeolite, polymer, and activated carbon. Activated charcoal from mangroves becomes an alternative to natural adsorbents with a large surface area. The ability of activated charcoal as an adsorbent was the focus of this study, both by the activation process by Fe cations and the addition of hydrogen peroxide activators. Characterization using a UV-Vis spectrophotometer is performed to see changes in indigosol concentration during the adsorption process. Results have shown that charcoal with Fe and H2O2 give a better performance on adsorption of indigosol than pure charcoal. Removal of indigosol by charcoal + Fe and H2O2 can reach 51%.